PEMBELAJARAN MENDALAM SEBAGAI STRATEGI PENGEMBANGAN KOMPETENSI SISWA SDN PANGARANGAN 1 - Yeni Puji Astutik; Lini Qinayah; Diva Fazhila; Rifatus Safira; Purnama Agustini; Amrotul Amilia; Putri Putri; Noro Zainur Rohmana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Twenty-first century learning requires the development of students’ critical thinking, creativity, collaboration, and communication skills at the elementary school level. The implementation of the Merdeka Curriculum initiated by the Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi encourages student-centered learning and emphasizes meaningful and in-depth conceptual understanding. This study aims to describe the implementation of deep learning as a strategy for developing student competencies at SDN Pangarangan 1 and to analyze its impact on improving conceptual understanding, critical thinking skills, and collaborative abilities. The study employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The research subjects consisted of two classroom teachers and 48 fourth- and fifth-grade students. The findings indicate that the implementation of deep learning improved students’ conceptual understanding, as evidenced by 78% of students being able to explain the material in their own words and relate it to real-life contexts. Additionally, 72% of students demonstrated increased active participation in group discussions and improved critical thinking skills in responding to reflective questions. However, several challenges were identified, including limited instructional time and variations in students’ academic abilities. Overall, deep learning proved to be an effective strategy for developing elementary students’ competencies and is highly relevant to the objectives of the Merdeka Curriculum.